Sosialisasi Peran Perencana Sipil dalam Pembangunan di Desa Aursati - Febryanto; Adeswastoto, Hanantatur; Kaswara, Afdhal (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2024)
This activity aims to increase the understanding of the Aursati Village community about the importance of the role of civil planners in supporting village development. Socialization is provided in the form of training and participatory discussions with residents and village officials. The problems faced by the community include a lack of understanding of the role of civil planners and minimal involvement in the development planning process. Through this activity, material was presented regarding the function of civil planners, examples of village development projects were delivered, and an open dialogue was held to explore local infrastructure needs. The results of the activity showed an increase in community knowledge of the duties and contributions of civil planners in development. In addition, the community began to realize the importance of involvement from the early stages of planning. This activity also succeeded in building better communication between the community and technical parties, so that in the future it is hoped that sustainable synergy will be created in the village development process based on the real needs of the community